The Economic Costs of Hybrid Wars: The Case of Ukraine - Julia Bluszcz; Marica Valente (Defence and Peace Economics, 2020)
With more than ten thousand casualties, the ongoing hybrid Ukrainian war between pro-Russian separatists and the government in the Donbass region, Ukraine's productive core, has taken a severe toll on the country. Using cross-country panel data over the period 1995–2017, this paper estimates the causal effects of the Donbass war on Ukraine's GDP. Our counterfactual estimation by the synthetic control method shows that Ukraine's per capita GDP foregone due to the war amounts to 15.1% on average for 2013–2017. Separate analysis for the affected regions of Donetsk and Luhansk indicates an average causal effect of 47% for 2013–2016. Results are robust to pre-war confounds, namely, the Orange Revolution and Ukrainian-Russian gas disputes. As such, we discuss mechanisms underlying the war's causal effects on economic performance, which is of broader relevance for debates on the role of government in hybrid conflict management.
Keywords: C21; F5; O41; O47; 330; Hybrid conflict; economic costs; Ukraine crisis; synthetic control; conflict management